Nonequilibrium thermodynamics and optimal cooling of a dilute atomic gas - Mayer, Daniel; Schmidt, Felix; Haupt, Steve; Bouton, Quentin; Adam, Daniel; Lausch, Tobias; Lutz, Eric; Widera, Artur (Physical Review Research, 2020)
Characterizing and optimizing thermodynamic processes far from equilibrium is a challenge. This is especially true for nanoscopic systems made of a few particles. We here theoretically and experimentally investigate the nonequilibrium dynamics of a gas of a few noninteracting cesium atoms confined in a nonharmonic optical dipole trap and exposed to degenerate Raman sideband cooling pulses. We determine the axial phase-space distribution of the atoms after each Raman cooling pulse by tracing the evolution of the gas with position-resolved fluorescence imaging. We evaluate from it the entropy production and the statistical length between each cooling step. A single Raman pulse leads to a nonequilibrium state that does not thermalize on its own, due to the absence of interparticle collisions. Thermalization may be achieved by combining free phase-space evolution and trains of cooling pulses. We minimize the entropy production to a target thermal state to specify the optimal spacing between a sequence of equally spaced pulses and achieve in this way optimal thermalization. We finally use the statistical length to verify a refined version of the second law of thermodynamics. Altogether, these findings provide a general theoretical and experimental framework to analyze and optimize far-from-equilibrium processes of few-particle systems.
CRIS-Team Scopus Importer:2023-03-27